Are multiple directorships benefits or costs to Malaysia listed companies? - Kamardin, Hasnah (2012)
The objective of the study is to examine the extent of multiple directorships or outside directorships in Malaysian public listed companies (PLC).The benefits and costs of monitoring roles are proxied by the percentage of meetings’ attendance in board meetings.Attending meetings would provide directors with resources about the management decisions and would make them more effective in exercising their roles.The study uses a sample of 1023 directors from 134 companies in the Main Market of Bursa Malaysia in 2008. Results of the study show that the incidence of multiple directorships is low.Independent directors are found to have more multiple directorships as opposed to the executive directors who have the least number of multiple directorships.Directors with multiple directorships are older directors, have less director ownership and are in board with high fraction of independent directors.Based on the 75% cut-off for the percentage of meetings’ attendance, the logistic regression shows that multiple directorships have the likelihood to attend less board meetings but the relationship is not significant.Instead the tendency to be absent from board meetings is associated with the high number of board meetings.The tendency to attend more board meetings is also shown to be associated with the increase in age, tenure, and director ownership.The findings somehow have policy implication on the corporate governance practices.